THE BACTERIOLOGY OF OIL SARDINE (SARDINELLA LONGICEPS) AND MACKEREL (RASTRELLIGER KANAGURTA) CAUGHT FROM TROPICAL WATERS OFF COCHIN I- QUANTITATIVE ASPECTS - SURENDRAN, P K; GOPAKUMAR, K (Fishery Technology, 2017)
The total aerobic viable plate counts (TPCs) of skin, gills and intestine of newlycaught oil sardine (Sardinella longiceps) and Indian mackerel ( Rastrelliger kanagurta) at four different temperatures, namely 36 ± 1 oc, 28 ±2°C (RT), 8 ± 1 oc and 1 ±1 oc, are reported. The total plate count at RT of the skin of oil sardine and Indian mackerel were in the range of lOS to 107 and 104 to 106 per cm2, that of gills in the range of 105 to lOB and 104 to lOB per g and that intestine in the range of 10s to 109 and 105 to 108 per g respectively. The TPCs were markedly affected by the incubation temperature. Incubation at 28±2oC gave the highest count; at 36± 1 oc and 8 ± 1 oc, the counts decreased by nearly 1-2 log. cycles from that at RT. Incubation at 1 ± 1 oc registered the lowest count. The peak values for bacterial counts of these fishes occurred at different periods of the year.